Collaborative Communication for Inclusive Nutrition Access : A Case Study of Free Nutritious Meals Program (MBG) in Bandung Regency, Indonesia - Sarah Pamela; Mulharnetti Syas (Dealings Foundation Institute, 2026)
This study aims to analyze collaborative communication in the implementation of the Free School Lunch Program (MBG) in Bandung Regency, Indonesia. A descriptive qualitative approach with a case study design was used in this research. Data were collected through in-depth interviews, observations, and documentation, while data analysis utilized an interactive model consisting of data reduction, data display, and drawing conclusions. The results indicate that the Bandung Regency Government acts as the primary coordinator through governance strengthening, task force formation, and dashboard-based monitoring, while the media plays a role in disseminating information and ensuring transparency, and the community participates in monitoring and providing feedback. The findings indicate that the synergy among these three actors forms a triple-helix collaborative communication model that enhances the effectiveness of the sustainable implementation of the MBG program in Bandung Regency, Indonesia. The contribution of this research is to propose a collaborative governance-based communication model that integrates the government, media, and the public through digital monitoring and local supply chains to improve communication networks in the implementation of a sustainable MBG program.